Realization Strategy of Budget Allocation to Disseminating of Development Infomation - Tarmidzi Tarmidzi; Sahri Sahri; Hadi Mahmudi (Universitas Negeri Malang, 2018)
The objectives of this study is to know the strategy of realization for budget allocation of 2016 for disseminating of development information in news and communication Information Division, especially in Publication and Media Relation Sub Division at Public Relation and Protocol Bureau, Provincial Secretariat of West Nusa Tenggara. This study uses descriptive qualitative approach and tends to find a meaning from data obtained from the result of a research. It is intended to describe the description of existing data or theories and the resulting findings. In this case, the researchers collected data by conducting in-depth interviews and the use of information access test methods of eleven informants. The results show that there are limitations of publication budget on Sub Division of Publication and Media Relations at Public Relations Bureau and Protocol Provincial Secretariat of West Nusa Tenggara, the inappropriate use of the strategy, the lack of harmony of internal relations both within the environment of public relations officials themselves and with the media crew, the presumption that the Trip Press budget is in vain, less than the maximum use of media Internal and outdoor media.Keywords: Realization Strategy, Budget, Information and Development JEL Classification: G31, H73